1989
DOI: 10.1016/0014-5793(89)80808-7
|View full text |Cite
|
Sign up to set email alerts
|

Basic fibroblast growth factor enhances the capacity of bone marrow cells to form bone‐like nodules in vitro

Abstract: The role of basic fibroblast growth factor (bFGF) in the proliferation and differentiation of rat bone marrow cells in culture was studied. bFGF stimulated [3H]thymidine incorporation into these cells by 4-fold at a concentration of 0.3 ng/ml and half-maximal effect was observed at a concentration of 15 pg/ml. In addition to its mitogenic effect, bFGF stimulated alkaline phosphatase activity by 3.6-fold. Continuous treatment with bFGF (for 21 days) resulted in a 6.3-fold increase in the culture dish surface ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(39 citation statements)
references
References 14 publications
2
36
1
Order By: Relevance
“…Rat bone marrow stromal culture models have been used to demonstrate in vivo, the stimulatory effect of FGF-2 on bone formation (72)(73)(74). In vitro studies, using human bone marrow stromal cells, have shown that FGF-2 modulates the growth and expression of the osteogenic phenotype of human bone marrow-derived bonelike cells (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…Rat bone marrow stromal culture models have been used to demonstrate in vivo, the stimulatory effect of FGF-2 on bone formation (72)(73)(74). In vitro studies, using human bone marrow stromal cells, have shown that FGF-2 modulates the growth and expression of the osteogenic phenotype of human bone marrow-derived bonelike cells (75)(76)(77)(78).…”
Section: Discussionmentioning
confidence: 99%
“…FGF-9 can also increase OC gene expression and maintain Runx2 levels in calvarial cells (Fakhry et al, 2005). FGF-2 is also important in matrix mineralisation (Noff et al, 1989), and Fgf-2 −/− mice show a marked reduction in trabecular architecture, as well as decreased trabecular bone volume, mineral apposition, and bone formation rates (Montero et al, 2000).…”
Section: Fgfs In Controlling Osteoblast Phenotypementioning
confidence: 98%
“…In addition to their role in cell proliferation, FGFs are also known to affect the various stages of osteoblast differentiation, directly influencing the expression of various matrix proteins, including alkaline phosphatase (ALP) and osteocalcin (OC), as well as the transcription factor, Runx2. ALP is an early marker of osteoblast differentiation and its expression is enhanced by FGF-2 stimulation in rat bone marrow precursor cells (Noff et al, 1989;Pitaru et al, 1993;Zhang et al, 2002). Runx2, also known as cbfa-1, is a member of the Runt-related family of transcription factors and has been shown to be essential for both skeletal patterning during embryogenesis and the progression of osteoblast differentiation (Ducy et al, , 1999Komori et al, 1997).…”
Section: Fgfs In Controlling Osteoblast Phenotypementioning
confidence: 99%
“…The reason for the redundancy of the functional roles of FGFR2IIIc with the S252W mutation in the osteoblastic cells still remains unclear, but one possible explanation might be the species difference in the osteoblastic cells or the difference in the cell maturational stages (25). For example, FGF signaling generally causes potent mitogenic activity and reduces the ALP activity and type I collagen expression in osteoblastic cells (45)(46)(47), whereas it increases the ALP activity and matrix mineralization in bone marrow stromal cells (48,49) and promotes osteogenic responses in mesencephalic neural crest cells (50). On the other hand, the implantation of FGF2-soaked beads in the coronal suture results in increased osteogenic differentiation in vivo (19).…”
Section: Discussionmentioning
confidence: 99%